Rancang Bangun Sistem Informasi Pendataan Obat Pada Apotek Berbasis Website - Indra Ramadhan; Hibatullah Faisal; Firman Noor Hasan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Wailola Farma Pharmacy is a type of business in the field of health services. This pharmacy provides various products or types of medicines ranging from common drugs to hard drugs that must use a doctor's prescription. This pharmacy also provides examination services for several diseases such as cholesterol, uric acid, high blood pressure, and diabetes. Established in 2014 in Bula District, East Seram Regency, Maluku Province. The problem that occurs is that the system is still done manually, such as checking drug stocks one by one. Thus, if the customer wants to buy medicine, the employee must check the stock of medicine directly to the warehouse.  Sales data collection still uses a notebook. This research involves comprehensive stages in the system development process, starting from understanding user needs, analyzing needs, system design, to implementation and testing. The method used is the waterfall method, this method follows a structured, sequential, and gradual process starting from the communication process, followed by the planning process, then the modeling process, the construction process and ending with the implementation process. The result of the research is a drug data collection information system in a pharmacy that displays a main page interface that can make it easier for employees to monitor daily reports on drug purchases and sales, displays a drug page interface that can easily manage drug data, displays a supplier page interface to manage supplier data, make drug purchases to suppliers on the purchase page, and make drug sales on the sales page. In addition, this system also ensures data security by storing it online in a database. The existence of this information system positively contributes to improving services to consumers. This information system has passed the black box testing stage